PERAN KOMITE PEMBELAJARAN DALAM PENGAMBILAN KEPUTUSAN KURIKULUM MERDEKA DI SD DARUSSALAM BLOKAGUNG - Jamil, Sabarun; Khaudli, M. Imam (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The main objective of this study is to analyze in depth the role of the learning committee in the decision-making process of the Merdeka Curriculum at SD Darussalam Blokagung. This study uses a qualitative case study approach to analyze the role of the learning committee in the decision-making process of the Merdeka Curriculum at SD Darussalam Blokagung. Data was collected through participatory observation, in-depth interviews with the school principal, committee members, teachers, and parents, as well as documentation of meetings and curriculum documents. Data analysis was conducted using a descriptive-qualitative approach based on the Miles and Huberman model (data reduction, presentation, and conclusion). Data validity was strengthened through triangulation of sources and techniques to obtain a comprehensive and contextual picture in line with the character of the boarding school. The results of this study indicate that the learning committee at SD Darussalam Blokagung plays a strategic role in the implementation of the Merdeka Curriculum, namely as a mediator between the school and the community, an active participant in planning, and a reflective partner in curriculum evaluation. This role is not merely administrative but reflects genuine and contextual social involvement, particularly within the boarding school environment. Implications suggest that schools need to strengthen participatory partnerships with the committee to develop a relevant and inclusive curriculum. These findings also serve as a crucial foundation for enhancing the committee's capacity as a strategic agent in transformative educational management.